2004
DOI: 10.1073/pnas.0404632101
|View full text |Cite
|
Sign up to set email alerts
|

The T cell antigen receptor expressed by Vα14iNKT cells has a unique mode of glycosphingolipid antigen recognition

Abstract: Natural killer (NK) T cells with an invariant V␣14 rearrangement (V␣14i) are the largest population of lipid antigen-specific T lymphocytes identified in animals. They react to the glycolipid ␣-galactosyl ceramide (␣-GalCer) presented by CD1d, and they may have important regulatory functions. It was previously shown that the V␣14i T cell antigen receptor (TCR) has a high affinity for the ␣-GalCer͞CD1d complex, driven by a long half-life (t 1/2 ). Although this result could have reflected the unique attributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 40 publications
5
74
0
Order By: Relevance
“…However, the importance of these two positions for TCR contact is strongly suggested by their effects on antigenic potency. For example, ␣-glucosylceramide, which differs from ␣-GalCer only with regard to the orientation of the 4Ј-OH is a less potent antigen with a 10-fold reduced affinity for the TCR when bound to CD1d (28). Similarly, the 6Ј-COOH reduces the antigenic potency and TCR avidity compared with galactose, as detailed above.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the importance of these two positions for TCR contact is strongly suggested by their effects on antigenic potency. For example, ␣-glucosylceramide, which differs from ␣-GalCer only with regard to the orientation of the 4Ј-OH is a less potent antigen with a 10-fold reduced affinity for the TCR when bound to CD1d (28). Similarly, the 6Ј-COOH reduces the antigenic potency and TCR avidity compared with galactose, as detailed above.…”
Section: Resultsmentioning
confidence: 96%
“…The combined data indicate that modifications to the ceramide backbone in the bacterial antigen have a substantial influence on antigenic potency and overall avidity of the trimolecular interaction of TCR, glycolipid, and CD1d. Previously, we showed that absence of the 4-OH alone had a relatively small influence on antigenic potency and a Ͻ5-fold effect on equilibrium binding of a soluble TCR or binding of CD1d tetramers loaded with this variant glycolipid to live cells (28). The shorter C 8 acyl chain of PBS-25 and a C 14 analog of ␣-GalCer also did not cause a great decrease in antigenic potency (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…CD1d-reactive T cell hybridomas with an invariant V␣14i T cell antigen receptor ␣ chain have been described (27). T cell hybridomas were stimulated with the indicated glycolipids that were added either to plates coated with soluble CD1d, or with CD1d-transfected A20 B lymphoma cells, according to published protocols (28).…”
Section: Hybridoma Assaymentioning
confidence: 99%
“…The sugar linked to the sphingoid base plays a prom-inent role in the molecular determinant recognized by the iNKT cell TCR, with a galactose, in most cases, being the most potent moiety (Fig. 1C) (18). Although ␣-linked sugars (Fig.…”
Section: Presentation Of Gsls By Cd1dmentioning
confidence: 99%